Cosmetic Tourism: Bodies and Identities between New Opportunities and Unseen Risks / Turismo cosmético: cuerpos e identidades ante nuevas oportunidades y riesgos inéditos - Corbisiero, Fabio; Mónaco, Salvatore (Bajo Palabra, 2017)
Abstract: Unlike of what occurred in the industrial era, in the post-modern society the identity of the social actors is no longer linked only to the class, but it appears as the result of an individual choice. This process has been –and continues to be– favored by globalization, the growing free time, the spread and the multiplication of media and transportation tools, that offer possible new dimensions for the construction of self, that can be realized through the physical transformation too. This paper pretends to highlight how today even tourism can be an experience of identity construction. In particular, the contribution intends to describe a specific kind of tourism, the cosmetic one, whose aim is to combine the experience of traveling with the modification of the body which is a visible vehicle of identity. The purpose of the article is to show new opportunities –but also unseen risks– linked to this specific form of tourism. Keywords: post-modernism, identity, body, tourism, cosmetic tourism, globalization. Resumen: A diferencia de lo que ocurría en la era industrial, en la sociedad postmoderna la identidad de los actores sociales no está vinculada solo a la clase, sino que aparece más como el resultado de una elección individual. Este proceso ha sido –y sigue siendo– favorecido por la globalización, el creciente tiempo libre, la difusión y la multiplicación de los medios de comunicación y de transporte que ofrecen nuevas posibles dimensiones para la construcción del yo, que puede realizarse también a través de la transformación física. El artículo se propone mostrar que hoy también el turismo puede ser un momento de construcción de la identidad. En particular, este artículo describe un tipo específico de turismo, el cosmético, cuyo objetivo es combinar la experiencia de viajar con la modificación del cuerpo, que es un vehículo visible de nuestra identidad. El propósito de este trabajo es mostrar nuevas oportunidades –pero también riesgos inéditos– vinculados a esta forma específica de turismo. Palabras claves: post-modernismo, identidad, cuerpo, turismo, turismo cosmético, globalización.